No Effects of Photobiomodulation on Prefrontal Cortex and Hippocampal Cytochrome C Oxidase Activity and Expression of c-Fos Protein of Young Male and Female Rats - Gutiérrez-Menéndez, Alba; Martínez, Juan A.; Méndez, Marta; Arias, Jorge L. (Frontiers in Neuroscience, 2022)
The role of light in our biological processes and systems is extensively known. In addition, the use of light devices has been introduced in the field of healthcare as an opportunity to administer power light at specific wavelengths to improve our body functions and counteract light deficiency. One of these techniques is photobiomodulation (PBM), which uses red to infrared light in a non-invasive way to stimulate, heal, regenerate, and protect tissue. The main proposed mechanism of action is the stimulation of the cytochrome c oxidase (CCO), the terminal enzyme in the mitochondrial electron transport chain. PBM has achieved positive effects on brain activity and behavioral function of several adult animal models of health and disease, the potential use of this technique in developing stages is not surprising. This research aims to examine the effects of PBM on the prefrontal cortex and hippocampus of 23 day-old healthy male (n = 31) and female (n = 30) Wistar rats. Three groups of each sex were used: a PBM group which received 5 days of PBM, a device group submitted to the same conditions but without light radiation, and a control basal group. CCO histochemistry and c-Fos immunostaining were used to analyze brain metabolic activity and immediate early genes activation, respectively. Results displayed no metabolic differences between the three groups in both sexes. The same results were found in the analysis of c-Fos positive cells, reporting no differences between groups. This research, in contrast to the PBM consequences reported in healthy adult subjects, showed a lack of PBM effects in the brain markers we examined in young healthy rat brains. At this stage, brain function, specifically brain mitochondrial function, is not disturbed so it could be that the action of PBM in the mitochondria may not be detectable using the analysis of CCO activity and c-Fos protein expression. Further studies are needed to examine in depth the effects of PBM in brain development, cognitive functions and postnatal disorders, along with the exploration of the optimal light parameters.